Bioequivalence Study with Two Different Oral Formulations of Methocarbamol in Healthy Subjects - Schlegelmilch, Ronald; Eydeler Urte, A; Barkworth, Martin; Radeke, Anika (Arzneimittelforschung, 2009)
The objective of this study was to compare the pharmacokinetic profile of a new oral methocarbamol (CAS 532-03-6) formulation (DoloVisano® Methocarbamol 750 mg Tabletten) to that of a registered reference product and to demonstrate the bioequivalence of the formulations with respect to rate and extent of methocarbamol exposure.This bioequivalence trial was based on an open-label, single-dose, randomized, two-treatment, two-period crossover design. In each period 32 male or female healthy white volunteers received 2 tablets (2 × 750 mg methocarbamol) of either the test (a) or the reference (b) product after an overnight fasting of at least 12 h. Breakfast was served 4 h after dosing. The two treatment sequences were separated by a wash-out phase of 6 days. Blood samples were drawn prior to the first single administration and at 20 time points over 16 h thereafter, in order to create a pharmacokinetic profile. Adverse events were recorded at predefined time points during the study period.After a single dose of 1 500 mg methocarbamol the extent of exposure as well as the exposure rate for the test and the reference product were in good agreement. The extent of exposure in terms of AUC0–tz amounted to 58.43 µg/ml • h for the test product and to 58.21 µg/ml • h (geometric means) for the reference. Cmax reached values of 23.71 µg/ml for test and 23.32 µg/ml (geometric means) for the reference. The ratio and the 90% confidence intervals of AUC0–tz (a/b: 100.38% [95.08%–105.96%]) and of Cmax (a/b: 101.68% [91.68%–112.77%]) lay well within the predefined acceptance range of 80–125%. These results strongly indicate that the formulations tested are bioequivalent and therefore exchangeable. During the study neither unexpected nor severe or serious adverse events were reported. Likewise there were no clinically relevant findings with respect to vital signs and ECG.In this study bioequivalence could be demonstrated with respect to rate and extent of methocarbamol exposure.
Keywords: CAS 532-03-6; Centrally acting muscle relaxants; DoloVisano®; Methocarbamol, bioequivalence, pharmacokinetics